The Effectiveness of Using ELSA Speak Application to Teach English Speaking Skills to High School Students - Asteriana, Wipen (Journal of English Education Forum (JEEF), 2025)
This study investigates the effectiveness of the ELSA Speak application in improving high school students’ English-speaking skills. A quasi-experimental design with one group pre-test and post-test was employed, involving 26 students of Grade XI at MA Al-Mubarak NW Sembalun. Students were assessed on pronunciation, fluency, grammar, vocabulary, and comprehension. Data were collected through pre-tests, post-tests, and semi-structured interviews. Quantitative analysis showed a significant improvement in speaking scores from a mean of 12.11 (pre-test) to 18.07 (post-test). A paired sample t-test confirmed the difference was statistically significant (p < 0.05). Qualitative findings revealed that students gained confidence, fluency, and motivation through interactive features and instant feedback of the app. These results demonstrate that ELSA Speak is an effective digital tool for enhancing students’ speaking proficiency and should be integrated into classroom practice. Future studies could explore the long-term effects of using ELSA Speak by conducting longitudinal research over multiple semesters. Additionally, comparative studies involving different age groups or diverse linguistic backgrounds would help determine the app’s adaptability and effectiveness across varied educational contexts.